2016
DOI: 10.22441/ijimeam.2016.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Screen Printed Reference Electrode Based on Charge Balance and Poly (Butyl Acrylate) Photocurable Mebrane

Abstract: This research focus on transforming the traditional design of reference electrode into all-solid-state reference electrode front-end using Ag/AgCl screen-printed electrodes. By replacing the internal reference solution of a traditional reference electrode by a solid photocurable membrane, an all-solid-state reference electrode can be achieved. The solid-state screen-printed reference electrode was designed using a photocurable acrylic film containing immobilized sodium tetrakis [3,5-bis(trifluoromethyl)phenyl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Since the potassium ion sensor would have functioned as a pseudo-reference electrode, this electrode's stability performance was compared to the previously reported solid-state reference electrodes. By referring to Table 3, it was found that the pseudo-reference electrode in this work showed comparable duration time of stability except for the reference electrode reported by Alva et al [29]. Compared with this electrode (5 h), this study's pseudo-reference electrode revealed a more prolonged duration time of stability (10 h).…”
Section: Performances Assessment Of Potassium Ion Sensor For Pseudo-rsupporting
confidence: 60%
See 3 more Smart Citations
“…Since the potassium ion sensor would have functioned as a pseudo-reference electrode, this electrode's stability performance was compared to the previously reported solid-state reference electrodes. By referring to Table 3, it was found that the pseudo-reference electrode in this work showed comparable duration time of stability except for the reference electrode reported by Alva et al [29]. Compared with this electrode (5 h), this study's pseudo-reference electrode revealed a more prolonged duration time of stability (10 h).…”
Section: Performances Assessment Of Potassium Ion Sensor For Pseudo-rsupporting
confidence: 60%
“…1 mV/h [48]. Therefore, this system displays good stability in the first 10 h. The leaching of lipophilic salt caused a higher drift of potential differences after 10 h, KTClPB from the pseudo-reference electrode, and NaTFPB from aluminium ion sensor into aqueous solution [29]. The leaching of anion lipophilic from the membrane pBA caused the sensors to become less sensitive to their analyte ions.…”
Section: Stabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…High selectivity with low interference from other anions (>9 mV in a very wide concentration range) [79]…”
Section: Metallized Hole Pvc Membranementioning
confidence: 99%